An epidemic of bladder cancer: ten cases of bladder cancer in male Japanese workers exposed to ortho‐toluidine. Issue 4 (25th July 2018) - Nakano, Makiko; Omae, Kazuyuki; Takebayashi, Toru; Tanaka, Shigeru; Koda, Shigeki
Abstract : Background: ortho ‐Toluidine (OT) was listed as a Group 1 carcinogen by the International Agency for Research on Cancer in 2012 based on epidemiological observations of workers co‐exposed to OT and aromatic amines. From 2014 to 2017, several cases of bladder cancer (BCa) secondary to occupational exposure, primarily to OT, were detected in Japan. Objective: To describe 10 cases of BCa in male Japanese workers exposed primarily to OT at two plants that produce organic dye and pigment intermediates. Methods: Details of the 10 cases were obtained from company records and through a questionnaire and interview. The surrogate level of exposure to each aromatic amine was calculated as the total job‐weight/month for each process for each job‐year. Results: No quantitative exposure data were available. In most cases the surrogate level of exposure to OT was higher than to other amines. All 10 cases were exposed primarily to OT and co‐exposed to para toluidine, ortho ‐anisidine, aniline, 2, 4‐xylidine or ortho chloroaniline. The age range at diagnosis was 41‐71 years (mean 56). The duration of OT exposure was 7‐28 years (mean 16.5) . Disease latency was 16‐28 years (mean 21.9) . Eight patients were smokers. The main symptom at diagnosis was hematuria (70%). Conclusions: The characteristics of BCa cases were associated with a high surrogate level of OT exposure and a disease latency of more than 20 years from the initial OT exposure. The main route of OT exposure was likely through the skin. It is necessary to continue health examinations in these target groups.